NITRATE AND NITRITE CONCENTRATIONS MEASUREMENT BASED ON IMAGE PROCESSING TECHNIQUE WITH COLOR INTENSITY APPROACH IN SURFACE WATER - Fortunata Wijaya, Clara
Surface water quality becomes a concern especially with the increasing of water pollution. Before being used, pollutants concentration measurement is needed to design the right treatment. Pollutants measurement method that is often used, using spectrophotometer UVVis, requires sample preparation process and the measurement has to be done in laboratory. This kind of method in a certain duration can be not efficient because pollutants concentration might be changed as time goes by. To shorten the time needed for measuring pollutants concentration, measurement with image processing method is developed with less effort sample preparation and less cost instruments. This study is focused on nitrate (NO3 - ) and nitrite (NO2 - ) concentrations measurement with color intensity approach through Plugable Digital Viewer and Microsoft Excel to obtain color components value such as GI, hue, and saturation. Highest correlation obtained between nitrate concentration and color component value is R2 = 0,9963; meanwhile highest correlation obtained between nitrite concentration and color component value is R2= 0,9816. Comparation test results obtained with spectrophotometry method indicated there are no significance differences between measurement results, observed from p-value >0,05 on confidence level 95%. This study concludes that image processing technique can be used as a trusted nitrate and nitrite concentrations measurement.